1989
DOI: 10.1016/0014-5793(89)80570-8
|View full text |Cite
|
Sign up to set email alerts
|

Low‐molecular‐mass proteins in cyanobacterial photosystem II: Identification ofpsbH andpsbK gene products by N‐terminal sequencing

Abstract: The O,-evolving photosystem II core complex was isolated from a thermophilic cyanobacterium, Synechococcus vulcanus Copeland. Analysis by SDS-polyacrylamide gel electrophoresis revealed that the complex contained at least seven lowmolecular-mass proteins in addition to the well characterized CP47 apoprotein, CP43 apoprotein, 33 kDa extrinsic protein, Dl protein, D2 protein and large subunit of cytochrome b-559. The separation profiles of these low-molecular-mass proteins were very similar between cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…This pattern is almost identical with our previously reported profile [10], except for the absence of a minor band of 4.4 kDa. In many cases, the 4.4 kDa protein was not recovered in OE-eVolving core complex and may well be no real PS II component.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This pattern is almost identical with our previously reported profile [10], except for the absence of a minor band of 4.4 kDa. In many cases, the 4.4 kDa protein was not recovered in OE-eVolving core complex and may well be no real PS II component.…”
Section: Resultssupporting
confidence: 91%
“…In the previous paper, we reported that the O2-evolving PS II core complex of Synechococcus vulcanus contains many low-molecular-mass components like higher plants, and confirmed the presence of the psbH and psbK gene products by N-terminal sequencing [10]. We also detected the gene products ofpsbI and psbL as well as psbE and psbF in the cyanobacterial reaction center complex [11].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…This method enabled discrete detection of many lowmolecular-mass components in the PS II complex [23][24][25], which could not be resolved by conventional SDS-PAGE, The resolved proteins were electroblotted to PVDF ~membrane, and directly subjected to amino acid Sequencing. By use of this method, the N-terminhl partial amino acid sequences of many new PS II components have been determined [24][25][26] ....…”
Section: Introductionmentioning
confidence: 99%